Property intervention in Southern Baja California during the Mexican Revolution: its impact on economy (Tzintzun, Revista de Estudios Históricos, 2016)
he present paper seeks to explain the impact of the Mexican Revolutionon the economy of the Southern District of Baja California, concerningthe intervention and use of property accumulated by the revolutionarygroups. It will be pointed out that it did not extend all theway along the District, neither did it reach all economic sectors, and itresponded to political and business payments. Exempt from propertycontrol were those owners who stayed in a relatively marginal positionin the ight for power, as well as those who showed willingness to supportthe military faction that dominated the region.
Keywords: property operation; Southern District of Baja California; Gastón J. Vives; Miguel L. Cornejo; Félix Ortega